2002
DOI: 10.1074/jbc.m111285200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of a New Class of Allosteric Effectors Complexed to Tryptophan Synthase

Abstract: Allosteric effectors are defined as compounds that influence protein function by binding to a site distant to the functionally affected site. The mechanism of action is based on the stabilization of alternative tertiary or quaternary structures, depending on protein subunit composition. A paradigm of allosteric effectors is 2,3-diphosphoglycerate that binds to the central cavity of hemoglobin and decreases oxygen affinity by stabilizing the T state (1). In monomeric proteins noncompetitive inhibitors can be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 43 publications
3
54
0
Order By: Relevance
“…The second catalytically important amino acid ␣Glu 49 is modeled in two conformations and forms a hydrogen bond with the IAG acetyl oxygen atom. The implications of this interaction for the ␣-reaction are discussed in the accompanying paper (24). The hydrogen bonding patterns and distances are shown in Fig.…”
Section: Iag Structurementioning
confidence: 95%
See 2 more Smart Citations
“…The second catalytically important amino acid ␣Glu 49 is modeled in two conformations and forms a hydrogen bond with the IAG acetyl oxygen atom. The implications of this interaction for the ␣-reaction are discussed in the accompanying paper (24). The hydrogen bonding patterns and distances are shown in Fig.…”
Section: Iag Structurementioning
confidence: 95%
“…IAG binds to the mutant in the same manner as to the wild-type (24), but loop ␣L6 is not closed. The indole nitrogen forms a hydrogen bond with aspartate ␣Asp 60 and the acetyl carboxylate group mimics the IGP/IPP/GP phosphate group.…”
Section: Iag Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Among the 21 protein family pairs, only two are known to interact based on experimentally resolved cocrystal structures: TrpA−TrpB [PDB 1k7f (34) (Fig. 4).…”
Section: Simultaneous Identification Of Interacting Families and Specmentioning
confidence: 99%
“…Al, 2000). The crystal structures of tryptophan synthase complexed with indole-3-acetylglycine and indole-3-acetyl-l-aspartic acid revealed that both ligands bind to the active site such that the carboxylate moiety is positioned similarly as the phosphate group of the natural substrates (Weyand et al, 2002).…”
Section: Research For Finding New Target Sitesmentioning
confidence: 99%